DISTRIBUSI FAKTOR PRODUKSI: Pemerataan Kesejahteraan Ekonomi melalui Distribusi Faktor Produksi - AM Hafidz MS (Jurnal Hukum Islam, 2010)
It is hard to deny that ownership of production factors should be fairly and proportionately distibuted. It will enable every economic agent to deliver maximum output and raise their revenue due to their participation in production process. Thus, it requires that distribution is just not dwell on the income distribution but also on the production factors. This paper seeks to describe the theory proposed by Islamic economy in the sake of production factors.